Enhancing parent-child relationship through dialogic reading. Issue 1 (1st January 2017) - Ganotice, Fraide A.; Downing, Kevin; Mak, Teresa; Chan, Barbara; Lee, Wai Yip
Abstract: Dialogic reading (DR) has been identified as an effective strategy for enhancing children's literacy skills in Western and Asian contexts. Given that storytelling is a shared experience between adults and children, parent–child relationships is hypothesised to be enhanced by DR. Despite this possibility, there has been no systematic attempt to examine the possible impacts of DR on the parent–child relationship. This study bridges this gap in the literature by studying the relationship between adults and children before and after training in the practice of dialogic reading techniques. Forty-eight Cantonese-speaking parents with children aged between 3 and 12 were recruited from schools. They were assessed prior to and after undergoing a four-hour dialogic reading training programme with a two-hour follow-up session using the Parent–Child Relationship Inventory. The results of this study suggest that DR has considerable potential for improving parent–child relationships. The findings are discussed in relation to the situation of Chinese learners in the Hong Kong context.